Hubungan agama dengan kekerasan dan konflik - Sholihah, Nailatus (Maliki Interdisciplinary Journal, 2024)
Religion is a guide in human life, but in religious life violence and conflict in various contexts can occur. This article was prepared using a library research approach and aims to understand how religion relates to conflict and violence as well as religious patterns and issues in Indonesia. Conflict is a difference between two parties that aims to disturb the other party. Meanwhile, violence is behavior that forces or harms other parties physically, verbally, or psychologically. The relationship between religion and violence is divided into several forms, such as; identity conflict, historical conflict, territorial conflict, religious extremism, political conflict, and communal conflict. However, religion is also able to play its role in resolving these conflicts or violence. Patterns of religious conflict can change over time. An example of a religious issue that is very prevalent today is terrorism, which cannot be universally accepted. The pattern of religious conflict itself includes the type, frequency, development, and issues that cause religious conflict. The majority of existing conflicts are for peaceful actions or protests, and violent actions.